Genetic diversity and structure in ex situ conserved populations of Hevea brasiliensis - Silva, Murilo da Serra; Cambuim, Jose [UNESP]; Kuboyama Kubota, Thaysa Yuriko [UNESP]; Pupin, Silvelise [UNESP]; Alves, Rafael Moyses; Teixeira de Moraes, Mario Luiz [UNESP]; Goncalves, Paulo de Souza; Sebbenn, Alexandre Magno; Menezes Freitas, Miguel Luiz (Ipef-inst Pesquisas Estudos Florestais, 2019)
Using microsatellite loci, this study assesses the genetic diversity and structure and relatedness in two conserved ex situ Hevea brasiliensis populations in Selviria, Mato Grosso do Sul State, and Maraba, Para State, Brazil. The aim of the study was to determine the potential of these populations for breeding and conservation programs. The total number of alleles was lower in Selviria (100) than in Maraba (179 alleles), with an average of 6.7 and 11.9 alleles per locus, respectively. The expected heterozygosity (H-e), observed heterozygosity (H-o), and fixation index (F) were similar between populations, but allelic richness (R) was higher in Maraba. Genetic differentiation between populations (G'(ST)= 0.28) indicates that genetic diversity is mainly distributed within populations. The mean coancestry coefficient in each population was positive but close to zero (< 0.08), and when considering both populations together it was - 0.001. Therefore, crosses between individuals of these populations can be encouraged to promote heterotic effects through breeding. The results suggest that the studied populations can be used in both conservation and breeding programs.
Keywords: microsatellite markers; population genetics; rubber tree